2005
DOI: 10.1038/sj.leu.2403985
|View full text |Cite
|
Sign up to set email alerts
|

Activated natural killer cells from patients with acute myeloid leukemia are cytotoxic against autologous leukemic blasts in NOD/SCID mice

Abstract: Natural killer (NK) cells are implicated in the surveillance of hematological malignancies. They participate in the immune response against residual acute myeloid leukemia (AML) after hematopoietic stem cell transplantation with partial HLA class I disparity. However, the role of NK cells in autologous leukemia-specific immunity remains poorly understood. We studied the function of NK cells in AML patients at diagnosis. Following isolation, CD56+CD3- cells exhibited a high proliferative potential in vitro in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 49 publications
0
41
0
Order By: Relevance
“…32 In parallel, studies have decoded the crucial receptor-ligand interactions for recognition of more complex primary tumor targets including freshly isolated leukemic blasts. 41,42 NK-cell recognition of myeloma seems to depend primarily on DNAM-1, whereas recognition of AML primarily relies on NKG2D. 21 Similarly, a role for NKG2D has been suggested in NK cellmediated killing of the MDS clone.…”
Section: Discussionmentioning
confidence: 99%
“…32 In parallel, studies have decoded the crucial receptor-ligand interactions for recognition of more complex primary tumor targets including freshly isolated leukemic blasts. 41,42 NK-cell recognition of myeloma seems to depend primarily on DNAM-1, whereas recognition of AML primarily relies on NKG2D. 21 Similarly, a role for NKG2D has been suggested in NK cellmediated killing of the MDS clone.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, it has also been confirmed that NK cells derived from AML patients post therapy can be fully functional and that the altered NK cell phenotype is reversible. 25,26,41,76,79 Moreover, CD56 bright NK cells are strong cytokine-secreting cells, vital for the initiation of adaptive immunity and cell proliferation, hence attractive for the generation of sustained anti-leukemic immunity. 80 Altogether, this knowledge prompts further exploration of enforcing NK cells in AML patients that achieved complete remission.…”
Section: Nk Cell Immune Escape In Aml E Lion Et Almentioning
confidence: 99%
“…Downregulation of the activating receptors on NK cells from AML patients may explain the observed reduced NK killing of autologous AML cells and the HLA class I-deficient K562 cell line. 6,7,9,56 Unfortunately, the expression of the activating DNAM-1 receptor on NK cells from AML patients has not yet been analyzed. It has also been suggested that direct cell contact between leukemic blasts and NK cells rather than secretion of TGF-b 1 may induce downregulation of the NCRs.…”
Section: Nk Cells and Leukemia S Verheyden And C Demanetmentioning
confidence: 99%
“…53,55 An upregulation of NKG2D ligands on leukemic cells by growth factors could enhance NK cellmediated killing. 7 An overview of the expression of different NK activating ligands on AML cells is given in Table 3. Furthermore, Costello et al 6,56 demonstrated that the majority of NK cells in AML patients display a low NCR surface density correlating with their weak cytolytic activity against autologous leukemic cells.…”
Section: Nk Cells and Leukemia S Verheyden And C Demanetmentioning
confidence: 99%
See 1 more Smart Citation